Corps Accords. : Body Talk. - Fol, Carine; Veress, Tatiana; Bultiau, Olivier; Danchin, Laurent; Delvoye, François; Kröger, Michael; Lanoux, Jean-Louis; Lamarche, Caroline; Potié, Frédéric; Safarova, Barbara; Art & Marges Museum, Brussel (Brussel : Art & Marges Museum Brussel, 2010)
Bottemanne, Dominique ; Bourgeois, Louise ; Condylis, Philippe ; Lucas, Löic ; Nedjar, Michel ; Pelosi, Marinela ; Plny, Lubos ; Vermeesch, Dominique ; Wittkamp, Klaus
Corps Accords - Body talk, Art & Marges Museum, Brussel, 10.09 - 31.12.2010
kunstcatalogus